Effectiveness of trauma-focused treatment for adolescents with major depressive disorder. Issue 1 (31st December 2019) - Paauw, Corine; de Roos, Carlijn; Tummers, Judith; de Jongh, Ad; Dingemans, Alexandra
ABSTRACT: Background : Major Depressive Disorder (MDD) in adolescence has a high prevalence and risk of disability, but current treatments show limited effectiveness and high drop-out and relapse rates. Although the role of distressing experiences that relate to the development and maintenance of MDD has been recognized for decades, the efficacy of a trauma-focused treatment approach for MDD has hardly been studied. Objective : To determine the effectiveness of eye movement desensitization and reprocessing (EMDR) therapy as a stand-alone intervention in adolescents diagnosed with MDD. We hypothesized that reprocessing core memories related to the onset and maintenance of MDD using EMDR therapy would be associated with a significant decrease in depressive and comorbid symptoms. Method : We recruited 32 adolescents (12–18 years) fulfilling DSM-IV criteria for mild to moderate-severe MDD from an outpatient youth mental health care unit. Treatment consisted of six weekly 60-min individual sessions. Presence or absence of MDD classification (ADIS-C), symptoms of depression (CDI), symptoms of posttraumatic stress (UCLA), anxiety (SCARED), somatic complaints (CSI), and overall social-emotional functioning (SDQ) were assessed pre and post-treatment and 3 months after treatment. Results : 60.9% of the adolescents completing treatment no longer met DSM-IV criteria for MDD after treatment anymore, and 69.8% at follow-up. Multilevel analyses demonstrated significant posttreatment reductions of depressive symptoms (CDI: Cohen's d = 0.72), comorbid posttraumatic stress, anxiety and somatic complaints, while overall social-emotional functioning improved. These gains were maintained at 3-month follow-up (Cohen's d = 1.11). Severity of posttraumatic stress reactions significantly predicted the posttreatment outcome; however, duration of MDD, number of comorbid disorders, or having a history of emotional abuse, emotional neglect or physical neglect were not predictive for outcome. Conclusions : This is the first study suggesting that EMDR therapy is associated with a significant reduction of depressive symptoms and comorbid psychiatric problems in adolescents with mild to moderate-severe MDD. HIGHLIGHTS: Major Depressive Disorder (MDD) can be treated in adolescents using a trauma focused treatment approach. EMDR therapy is effective in adolescents with a primary diagnosis of MDD. Sixty percent no longer fulfilled the MDD diagnosis after 6 sessions of EMDR. Symptoms of anxiety, post-traumatic stress, somatic complaints also decreased significantly and overall social-emotional functioning improved.